We Don't Train in Vain: A Systematic Review and Meta-Analysis of Human and Canine Caregiver Training. Issue 3 (2nd July 2020) - Pfaller-Sadovsky, Nicole; Medina, Lucia; Dillenburger, Karola; Hurtado-Parrado, Camilo
ABSTRACT: The present review assessed the current knowledge regarding caregiver- training effectiveness for human and human-canine dyads. Most canine-related sources (66%; n = 19) were case studies reporting a decrease of learner undesired behavior when using oral instruction (21%; n = 6). Most human-related research used single-case designs (57%; n = 26) reporting an increase in desired learner behavior (22%; n = 10) when caregivers received multi-component training packages (17%, n = 8). The meta-analysis (n = 18) revealed that interventions had a large effect (Hedges' g = 0.88, 95%CI [0.68–1.07]), with packages yielding a slightly larger moderate effect (Hedges' g = 0.76, 95%CI [0.60–0.91]) than oral instruction alone (Hedges' g = 0.74, 95%CI [0.32–1, 15]). Although the effectiveness of caregiver training is promising, the results should be interpreted cautiously. Due to the preponderance of case studies within canine literature and the insufficient reporting of data across sources, only few studies could be included in the meta-analysis. Overall, more systematic and comparative research regarding the efficacy of caregivers in behavior change programs across species is needed.